Faktor-Faktor Yang Mempengaruhi Efektivitas Peran Lurah Dalam Penyelesaian Sengketa Tanah Di Kelurahan Benteng - muhammad ilham; Muhammad Rais Rahmat R; Akhmad Yasin (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Land disputes that frequently occur in Kelurahan Benteng, Baranti District, Sidenreng Rappang Regency, have become a significant issue affecting social order and community stability. This study aims to identify and analyze the factors influencing the effectiveness of the village head's role in resolving land disputes. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The results show that the effectiveness of the village head's role is influenced by eight main factors: work quality, knowledge, creativity, cooperation, resilience, initiative, personal qualities, and work quantity. These factors interact to affect the village head's performance as a mediator in resolving land disputes. A good understanding of land regulations and effective communication skills with the community are crucial in the mediation process. Additionally, the creativity and resilience of the village head in handling social and emotional challenges from the conflicting parties are key to successful mediation. Strong cooperation between the village head and related agencies such as the National Land Agency (BPN), as well as community leaders, further strengthens the village head's role as a neutral and trusted party. This study is expected to contribute to the development of the capacity of local government officials and the more effective resolution of land disputes in the future.